PELATIHAN PEMANFAATAN SAMPAH PLASTIK MELALUI PENGOLAHAN ECOBRICK SEBAGAI UPAYA EDUKASI LINGKUNGAN PADA ANAK-ANAK DI DESA PATOA - Rahmayanti; Ernawati; Syafriani (Jurnal Ilmu Sosial Terapan, 2025)
Waste management has become one of the major environmental challenges in coastal and rural areas, especially in remote regions. This community service activity aims to increase environmental awareness among children in Patoa Village through ecobrick training. Ecobrick is a method of reusing plastic waste by compressing it into plastic bottles to be used as a building material. The training was conducted in several stages: problem identification, planning, implementation, and evaluation. Children were involved directly in collecting plastic waste, learning about waste segregation, and practicing making ecobricks. The results showed that ecobrick training was effective in increasing children’s understanding of the plastic waste problem, fostering creativity, and encouraging active participation in maintaining environmental cleanliness. This activity also served as a form of early environmental education that could be replicated in other rural communities.